Comparison between solvent evaporation and supercritical CO2 technology in taste-masking of Azithromycin bitter-taste using pH-sensitive Eudragit EPO or Eudragit S100 polymers - Hadeia Mashaqbeh, Rana Obaidat, Mo’tasem M. Alsmadi, Tamara Athamneh (Journal of Applied Pharmaceutical Science, 2024)
Despite the broad spectrum of the antibiotic Azithromycin, its extremely bitter taste after oral dosing decreases patient compliance. This bitter taste can be masked by minimizing Azithromycin interaction with the tasting buds using polymers that are insoluble at salivary pH (6.8–7.4), like the cationic polymers Eudragit EPO and Eudragit S100. The purpose of this study was to employ two different techniques (solvent evaporation (SE) and supercritical fluid technology (SFT)) for encapsulating Azithromycin into Eudragit microparticles to mask its bitter taste. The formulations were characterized using Fourier-transform infrared spectroscopy (FTIR(, powder X-ray diffraction (PXRD), Differential scanning calorimetry (DSC), and scanning electron microscope (SEM). Also, the Azithromycin in vitro release and in vivo assessment of bitter taste masking were conducted. The present work showed promising results in veiling the bitter taste of Azithromycin. Taste panel scores for the in vivo clinical taste study of the formulation prepared using SE was 0.3 after 30 seconds compared to Azithromycin, resulting in a score of 3 owing to its palpable bitter taste. Whereas drug-Eudragit EPO showed no interaction, FTIR results indicated azithromycin interaction with Eudragit S100. The formulation prepared by the SE method and Eudragit EPO showed efficient taste masking, within-matrix encapsulation, lower drug release in simulated salivary fluid (SSF,
Keywords: Azithromycin dihydrate, taste masking, eudragit, solvent evaporation, supercritical CO2 technology